2022
DOI: 10.1097/bor.0000000000000858
|View full text |Cite
|
Sign up to set email alerts
|

Ribosome dysfunction in osteoarthritis

Abstract: Purpose of review Translation of genetic information encoded within mRNA molecules by ribosomes into proteins is a key part of the central dogma of molecular biology. Despite the central position of the ribosome in the translation of proteins, and considering the major proteomic changes that occur in the joint during osteoarthritis development and progression, the ribosome has received very limited attention as driver of osteoarthritis pathogenesis. Recent findings We provi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
27
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(30 citation statements)
references
References 65 publications
1
27
0
Order By: Relevance
“…We also investigated the changes in snoRNAs. From our previous study, we have known that snoRNAs have an important role in joint homeostasis ( 93 ), mouse joint ageing ( 17 ), chondrogenic differentiation ( 94 ), cartilage ageing ( 15 ), OA ( 6 , 7 ), and early OA SF ( 8 ). Interestingly, in the plasma, we found that 82% of DE snoRNAs in the plasma were also identified in ageing/OA human cartilage study ( 7 ), including Snord113/114, snord15, snord30, snord32/33, snord46, snord58, snord62, snord66, snord69, snord74, snord75, and U3.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We also investigated the changes in snoRNAs. From our previous study, we have known that snoRNAs have an important role in joint homeostasis ( 93 ), mouse joint ageing ( 17 ), chondrogenic differentiation ( 94 ), cartilage ageing ( 15 ), OA ( 6 , 7 ), and early OA SF ( 8 ). Interestingly, in the plasma, we found that 82% of DE snoRNAs in the plasma were also identified in ageing/OA human cartilage study ( 7 ), including Snord113/114, snord15, snord30, snord32/33, snord46, snord58, snord62, snord66, snord69, snord74, snord75, and U3.…”
Section: Discussionmentioning
confidence: 99%
“…Overall, the changes in snoRNAs in EVs in both the plasma and the SF provide an insight into their role in the pathogenesis of OA, as traditionally OA has been defined as an imbalance between joint anabolism and catabolism. With our increasing evidence that it is an acquired ribosomopathy ( 93 ), there is a potential role for EV-derived snoRNAs to contribute to OA pathogenesis via its cell communication role. We are currently studying sncRNA cross-talk in joint cells to shed more light on this hypothesis ( 99 ).…”
Section: Discussionmentioning
confidence: 99%
“…Overall the changes in snoRNAs in EVs in both plasma and SF provide insight into their role in the pathogenesis of OA as traditionally OA has been defined as an imbalance between joint anabolism/catabolism. With our increasing evidence that it is an acquired ribosomopathy (84), there is a potential role for EV-derived snoRNAs to contribute to OA pathogenesis via its cell communication role. We are currently studying sncRNA cross talk in joint cells to shed more light on this hypothesis (90).…”
Section: Discussionmentioning
confidence: 99%
“…We also investigated the changes in snoRNAs. From our previous work we know snoRNAs have an important role in joint homeostasis (84), in mouse joint ageing (16), in chondrogenic differentiation (85), in cartilage ageing (14), in OA (6, 7) and in early OA SF (8). Interestingly in plasma we found that 82% of the snoRNAs DE in plasma were also identified in ageing/OA human cartilage study (7), including Snord113/114, snord15, snord30, snord32/33, snord46, snord58, snord62, snord66, snord69, snord74, snord75 and U3.…”
Section: Discussionmentioning
confidence: 99%
“… 9 To date, the concepts of splicing and ribonucleic acid (RNA) editing consummate the GCD; meanwhile, entire information on DNA–RNA–protein processes is included. 10 , 11 GCD makes different contributions to many physical and pathological processes, including oncogenesis, 12 mechanical stress on human cells, 13 osteoarthritis, 14 and so on. However, the roles of GCD in the differentiation of stem cells remain unknown.…”
Section: Introductionmentioning
confidence: 99%